2022
DOI: 10.3390/ijerph19063648
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes toward Autism Spectrum Disorder in Saudi Arabia

Abstract: Aims: The diagnosis of autism spectrum disorder (ASD) is not easy as there is no direct test that exists to establish such a diagnosis. Increasing community and healthcare professional knowledge of the ASD spectrum is crucial because it will encourage parents of ASD children to seek screening and diagnosis from a specialist, allowing for better early detection and treatment. This study explored the knowledge of the general population in Saudi Arabia regarding ASD and assessed variables associated with an accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
3
19
0
3
Order By: Relevance
“…The current study found that there is no relation between total knowledge scores of women and their age. This was agreement with previously Saudi study by Alyami et al, (2022) indicted that the mean ASD knowledge score displayed no statistical difference between participants according to their age. On the other hand, Mousa et al, (2021) showed no significant differences were present in education level when correlated with knowledge about ASD and also, the same study detected significant association between the mothers' age and their knowledge, this contradiction between our study and the last study may be due to differences between participants characteristics as the latter study's participants were women with autistic children.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The current study found that there is no relation between total knowledge scores of women and their age. This was agreement with previously Saudi study by Alyami et al, (2022) indicted that the mean ASD knowledge score displayed no statistical difference between participants according to their age. On the other hand, Mousa et al, (2021) showed no significant differences were present in education level when correlated with knowledge about ASD and also, the same study detected significant association between the mothers' age and their knowledge, this contradiction between our study and the last study may be due to differences between participants characteristics as the latter study's participants were women with autistic children.…”
Section: Resultssupporting
confidence: 93%
“…The reliability of the knowledge quiz was assessed using Cronbach's alpha, and its result pointed to good internal consistency (r= 0.766). Part III: ASD attitude scale was adapted from the previous literature(Alyami et al, 2022; Liu et al, 2016). The scale comprises…”
mentioning
confidence: 99%
“…A previous study in Jordan revealed different findings that more than 80% of the Jordanian population have knowledge about cases and symptoms of epilepsy [ 14 ]. A recent study in Saudi Arabia showed consistent findings that the participants showed a weak level of knowledge about autism (34.7%), with a middle income category being less likely to be knowledgeable about autism compared to others [ 29 ].…”
Section: Discussionmentioning
confidence: 77%
“…This discovery corroborates other findings in the literature. Previous research demonstrates that females are more aware of autism than males [24]. One possible reason for this is that females are more interested in studying medical information than males [13,28,39,40], leading to a substantial difference in knowledge between males and females, as well as a stronger knowledge of specific illnesses and conditions in females [28].…”
Section: Discussionmentioning
confidence: 99%
“…When we examine levels of autism knowledge globally, we see vast differentiation between countries. Research shows that public knowledge of autism is particularly poor in Saudi Arabia [24], China [25,26], and Pakistan [27], but much better in countries, such as Australia [28], USA [25,29], Northern Ireland [30], and the UK [31]. Interestingly the countries that present with the greatest knowledge levels are the same countries in which autism education campaigns have been run, affirming the use and effectiveness of such campaigns.…”
Section: Introductionmentioning
confidence: 99%